2020
DOI: 10.1177/0149206320950439
|View full text |Cite
|
Sign up to set email alerts
|

From Strategic Leaders to Societal Leaders: On the Expanding Social Role of Executives and Boards

Abstract: Scholarship on strategic leadership and governance has long operated under the assumption that strategic leaders’ influence and purview are predominantly constrained by organizational boundaries. Recent events and social movements have called this limited view of strategic leadership into question, however. In this editorial commentary, we explore the emerging trend of strategic leaders becoming—in both their own and stakeholders’ perceptions—societal leaders advancing social change inside and outside their or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Managing up takes into account the larger political context. This expands the role of the supply chain manager to the one of a governor, lobbyist, and politician (see Krause & Miller, 2020). To bring us to a truly transformative interpretation of adaptive management (see Folke et al, 2010), managing beyond could be added as a more radical approach, which is about fundamentally challenging the structures and processes beyond the supply chain.…”
Section: Theme 1: Extending the Unit Of Analysismentioning
confidence: 99%
“…Managing up takes into account the larger political context. This expands the role of the supply chain manager to the one of a governor, lobbyist, and politician (see Krause & Miller, 2020). To bring us to a truly transformative interpretation of adaptive management (see Folke et al, 2010), managing beyond could be added as a more radical approach, which is about fundamentally challenging the structures and processes beyond the supply chain.…”
Section: Theme 1: Extending the Unit Of Analysismentioning
confidence: 99%
“…The video included the words: "There are two types of Americans that have emerged through this pandemic; Those who sacrifice and those who demand. " Mohammed et al (2021) reflected on corporations, politicians, and the public using such heroization of nurses' suffering for their own political, economic, and cultural ends, arguing that it amounted to a form of performative allyship, where those with decisional and economic power signal support, but fail to engage in the educational, self-reflexive, policy, and structural changes inherent in more genuine forms of allyship (Erskine and Bilimoria, 2019;Krause and Miller, 2020). Hall et al (2003) conducted content analysis of local and national news media documents to describe nursing work life issues as portrayed in the media during the SARS crisis in Toronto.…”
Section: And a Nurses Relativementioning
confidence: 99%
“…Indeed, our review revealed that extant research focused on exploring how individual themes of CEO tenure relate to financial outcomes. Thus, in line with related recommendations by, for example, Krause and Miller (2020), Barney (2020), and Lee et al (in press), CEO tenure research should broaden the scope to a variety of stakeholders and outcomes, such as organizational resilience (Ortiz-de-Mandojana & Bansal, 2016), corporate social performance (Bansal & Song, 2017), and societal and environmental impact (Nyberg & Wright, in press). For instance, considering organizational resilience as an outcome could inform our knowledge about CEO power and CEO human capital.…”
Section: Substantiating Knowledge Within Themesmentioning
confidence: 85%